1998
DOI: 10.1097/00005768-199802000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative intramuscular myoelectric activity of lumbar portions of psoas and the abdominal wall during a wide variety of tasks

Abstract: Consideration of deep muscle activity, provided in this report, is important for choosing the most appropriate rehabilitation and training program for an individual. Specific guidance is provided for choosing the best abdominal exercise, together with activation profiles during lifting, during twisting, and during hip rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
144
2
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(158 citation statements)
references
References 15 publications
7
144
2
5
Order By: Relevance
“…Conventionally, curl-up exercises are performed with the upper limbs bent at the elbow joints and hands placed on the chest. Studies have found that activity in the RA muscle varies for this version of the exercise from 50% [9] to 60% [11] of MVC, and is similar in both the lower and upper part of this muscle [12]. A similar result was obtained for this version of the exercise in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Conventionally, curl-up exercises are performed with the upper limbs bent at the elbow joints and hands placed on the chest. Studies have found that activity in the RA muscle varies for this version of the exercise from 50% [9] to 60% [11] of MVC, and is similar in both the lower and upper part of this muscle [12]. A similar result was obtained for this version of the exercise in our study.…”
Section: Discussionsupporting
confidence: 89%
“…The reason for using different trunk tasks is that they each involve unique combinations of abdominal muscle activity to move the trunk into a new orientation or stabilize the spine. 10,11 As individual abdominal muscles receive innervation from different thoracic segment levels, 12 the assessment of different abdominal muscles should help to further increase the diagnostic accuracy in identifying the specific level and completeness of the SCI. However, to our knowledge, no studies have examined the accuracy of using manual examination to determine abdominal muscle function in persons with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…The core muscles maintain the neutral pelvic position on the bike when the anterior and posterior muscle components are equally balanced. On the hasis of orientation and attachment of the psoas muscle on the lumbar spine, pelvic stabilization and resistance to fatigue are critical to maintain the natural curve of the spine as well as provide the leverage from which the psoas and gluteal muscles contract when a greater power output is required (8). Although the lack of core stability would appear to have the greatest influence on the back, lower extremity alignment could also be affected as the foundation from which power is generated becomes compromised (2).…”
Section: Introductionmentioning
confidence: 99%